Penerapan Teknik Slow Stroke Back Massage Terhadap Tekanan Darah Pada Lansia Hipertensi Di Kelurahan Joyotakan, Surakarta - Dita Kusuma Fatmawati; Tri Susilowati; Muhammad Natsir (An-Najat, 2024)
Background: Hypertension is often referred to as the Silent Killer, because it is a deadly disease with no symptoms. According to the World Health Organization (WHO) data in 2019, hypertension occurs in the age group 31-44 years (31.6%), 45-54 years (45,3%), 55-64 years (52.2%). One of the non-pharmacological therapies that can be done in hypertensive patients is Slow Stroke Back Massage. Slow stroke back massage has become one of the complementary therapy that is currently used to lower hypertension. Objective: To know the results of the implementation of Slow Stroke Back Massage therapy to reduce blood pressure in hypertensive patients in Joyotakan Village. Method: Using a descriptive method with a case study design approach, respondents use 2 hypertensive patients, determining respondents according to the inclusion and exclusion criteria is done for 3x in 1 week with a time of 3-10 minutes. Slow Stroke Back Massage and blood pressure measurement using sphygmomanometer. Result: Slow Stroke Back Massage was able to lower blood pressure in two respondents in Joyotakan Village. Conclusion: There was a decrease against 2 respondents after the Slow Stroke Back Massage therapy for 3x in 1 week.